P237 Lung function decline is associated with serum periostin level but not fractional exhaled nitric oxide or blood eosinophils in severe asthma. (15th November 2016) - Mansur, AH; Mitchell, V; Sullivan, J; O'Shea, K; White, L
Abstract : Background: In the airways, periostin encoded by the POSTN gene is up-regulated by IL13-IL4-TGF-β axis. It is produced by structural cells such as epithelial cells and fibroblasts and inflammatory cells such as eosinophils and macrophages. Consequently it has been linked to airways remodelling, mucus production and subepithelial fibrosis. However, an association between periostin and lung function impairment in severe asthma has not been confirmed. Methods: Unselected patients attending severe asthma centre were clinically characterised using systematic protocol and undergone lung functions, serum periostin, fraction exhaled nitric oxide (FeNO) and peripheral blood eosinophils (PBE) measurement. Correlation analysis and one way analysis of variance were undertaken to explore the relationships. Results: 127 patients consented to the study (mean age 45.5 yrs [range 17–70], 88 [69%] females), 72/103 (69%) were atopic. The mean FEV1 was 2 L, mean%predicted FEV1 68.1, and mean FEV1/FVC ratio was 71.3. The mean inhaled daily corticosteroids dose was 1.65mg/day and 56.3% were on maintenance oral corticosteroids. Periostin measurement was available in 78 patients who had a mean level of 49.5 ng/L (SD ± 18.1). Using 50 ng/L as a cut-off point, 30/78 (36%) patients had high periostin and 48/78 (62%) had low periostin. The mean FEV1 in the periostin high group was 1.69 L Compared to 2.15 L in the low group (p = 0.018) (see Figure ). We also observed significant correlation between serum periostin and% predicted FEV1 (r = 0.36, p = 0.0017). In contrast the association analysis between FeNO and PBE with FEV1 were both non-significant (p = 0.8 and p = 0.35 respectively). Conclusion: Raised serum periostin is associated with low lung function in this cohort of severe asthma but not FeNO or BPE. Further research is required to confirm this relation and explore the role of periostin as predictor of decline in lung function and airway remodelling.